CONCEPT OF APPLICATION OF WORKERS 'CONSTITUTIONAL RIGHTS JUSTICE OUTSOURCING - Mashari Mashari (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2019)
Indonesia as a state of law, which in the implementation of state power is carried outunder the rule of law. The logical consequence, the entire system of administration of stateadministration must be based on the constitution.1 Every implementation of state or government power is always built by and based on the principles and provisions of the constitution.The Indonesian Constitution states that the human rights of all citizens must not beviolated and must be fulfilled. The provisions of Article 1 paragraph (1) of Law Number 39 of1999 concerning Human Rights, which basically says that human rights are rights that areinherent and inherent in every person as God's creatures. As rights inherent in every humanperson, human rights are gifts that must be respected, upheld, guaranteed and protected by thestate, law and government, for the glory and protection of human dignity.